2016
DOI: 10.1590/2359-3997000000121
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar ataxia as presenting feature of hypothyroidism

Abstract: SUMMARYSymptoms and signs of the hypothyroidism vary in relation to the magnitude and acuteness of the thyroid hormone deficiency. The usual clinical features are constipation, fatigue, cold intolerance and weight gain. Rarely it can present with neurologic problems like reversible cerebellar ataxia, dementia, peripheral neuropathy, psychosis and coma. Hypothyroidism should be suspected in all cases of ataxia, as it is easily treatable. A 40 year-old male presented with the history facial puffiness, hoarseness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The search for a potentially treatable cause should include a broad spectrum of different disorders, and genetic evaluation should be considered only when other etiologies can be ruled out. Disorders commonly encountered in clinical practice such as vitamin B12 deficiency and hypothyroidism can occasionally cause ataxia and in rare cases present with it [ 2 , 3 ]. Adverse reactions to drugs (especially certain antiepileptic and chemotherapeutic agents), systemic autoimmune diseases (such as sarcoidosis, systemic lupus erythematous and Sjogren syndrome) [ 4 6 ], deficiencies of vitamin E and B1 (thiamine) as well as mineral deficiencies (such as copper or zinc) have all been occasionally linked with neurological symptoms, including ataxia [ 7 – 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The search for a potentially treatable cause should include a broad spectrum of different disorders, and genetic evaluation should be considered only when other etiologies can be ruled out. Disorders commonly encountered in clinical practice such as vitamin B12 deficiency and hypothyroidism can occasionally cause ataxia and in rare cases present with it [ 2 , 3 ]. Adverse reactions to drugs (especially certain antiepileptic and chemotherapeutic agents), systemic autoimmune diseases (such as sarcoidosis, systemic lupus erythematous and Sjogren syndrome) [ 4 6 ], deficiencies of vitamin E and B1 (thiamine) as well as mineral deficiencies (such as copper or zinc) have all been occasionally linked with neurological symptoms, including ataxia [ 7 – 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Carlè et al compared the efficacy of hypothyroidism-associated symptoms in predicting overt hypothyroidism in different age groups, and observed that only dyspnea, fatigue and wheezing were more prevalent in elderly patients (24). Hearing loss, ataxia, and dysgeusia are neurological symptoms frequently described in hypothyroid older patients (25). Especially among elderly, neuropsychiatric symptoms such as memory loss or depression (26), dermatologic or rheumatologic disorders (27), are commonly described and it is difficult to related them to hypothyroidism.…”
Section: Methodsmentioning
confidence: 99%
“…As the disease advances, the effect of thyroxine on reversibility of ataxia gradually decreases. 6,7…”
Section: Cerebellar Degeneration and Ataxiamentioning
confidence: 99%